Xyela helvetica - Blank, Stephan M.; Shinohara, Akihiko; Altenhofer, Ewald (Zenodo, 2013)
Xyela helvetica (Benson, 1961) Xyelatana helvetica Benson, 1961: 171, ♀, type locality: Switzerland, Grisons, Val Ftur, near Fuorn. Xyela helvetica : Rasnitsyn 1965: 492, 504, 514 (combination with Xyela ). Description . Female. Color. Head yellow with black and brown pattern: two black stripes along frontal furrows meeting dark ocellar and postocellar area, dark longitudinal spot in middle of frons and kidney-shaped spots on vertex. Antennae brown. Thorax dorsally predominantly dark with few pale markings on pronotum, mesonotal lobes and mesoscutellum, tegulae pale, mesepisternum largely pale brown. Abdominal terga dark brown, lateral parts of terga 8 and 9+10 brown or pale brown, valvifer 2 brown basally and dark distally, membrane between valvifer 2 and valvula 3 pale brown, valvula 3 brown with small pale ventral margin up to middle or farther (Fig. 86). Legs brown, femora with infuscate longitudinal stripes, ventral side of posterior coxae pale preapically. Wing membrane brownish infuscate, venation and pterostigma pale brown. Morphology. Fore wing 4.1–4.6 mm long, 1.20–1.35 times longer than ovipositor sheath, vein Rs+M 25–100 µm long, 2r-m meeting Rs 75–140µm distal to the furcation of Rs1 and Rs2. Synantennomere 3 740–790 µm long, antennomere 4 ca 240 µm long and ca 6.5 times longer than wide distally. Article 3 of maxillary palp 260–280 µm long, 0.75–0.80 times as long as scape and narrower than synantennomere 3. OOL: POL = 1.55–2.00: 1. Ovipositor sheath ca 3.40 mm long, valvula 3 2.9–3.1 times longer than valvifer 2 and 11.5–12.0 times longer than wide at base (Fig. 86). Valvula 3 of ovipositor sheath diamond-shaped in cross section, pale membranous area distally extending up to middle or even farther as small ventral pale margin of valvula 3, valvula 3 distally narrowing to acicular tip, tip without defined sensilla field, with 4–7 blunt setae (Fig. 86). Ovipositor almost straight. Valvula 1 of ovipositor compressed, medial part parallel-sided and longitudinally slightly bicolorous (presumably due to different degree of sclerotization of dorsal and ventral portions), aulax terminating almost at tip, ventral edge sloping up to tip in distal 0.1, with ca 10 wide-spaced annuli in distal 0.1 (basal 2 annuli only present close to aulax and distal continuous from aulax to ventral edge of valvula 1, basal oblique and distal 2 almost vertical), 4–5 shallow serrulae, olistether with 6–8 setae. Valvula 2 dorsally smooth and parallel-sided with regular shallow notches and indistinct vertical annuli in distal half, notches not evidently related to evenly spread sensilla campaniformia, dorsal edge of left and right valvula fused for most of their length up to triangular rise at 0.9 of ovipositor length, distal 0.1 of valvula 2 tapering to tip, with ca 7 oblique annuli. Posterior tibia 1.00– 1.05 mm long, all claws with delicate subapical tooth. Male. Unknown. Type material . Holotype ♀: [round label with red margin:] “ Type ”; “ Suisse — Gr. Val Ftur 23 IV 53 J. Aubert ”; “ Xyelatana helvetica sp. n. ♀ det. R. B. Benson 1960 ”; “ Xyela helvetica (Benson) ♀ det. S. M. Blank 2000”. Right antennal flagellum and parts of posterior tarsi missing. BNMC. Host plant . Ο Pinus mugo Turra, P. sylvestris L. (Schedl 1978). Geographic distribution . Austria, Switzerland (Fig. 19). Remarks . Females are distinguished from Xyela longula by the shorter ovipositor and the almost evenly pale colored valvula 1. See also remarks under X. longula . The male of X. helvetica remains unknown. The supposal of Viitasaari (1980) and Blank (2002) that the male reported by Schedl (1978) as X. longula from Hohe Wand (Lower Austria, NMW) belongs to X. helvetica cannot be confirmed here. In this male the valviceps is quite shallowly excised on its lower edge and the tip of the longer flagellum reaches 0.85 of the width of the distal lobe. However, study of a longer series of longula males reveals now that the morphological features of this specimen fall within the variability of X. longula . Thus the former identification of Schedl (1978) was correct, and the male X. helvetica remains undescribed. The collection data of the only two known females indicate an occurrence in the subalpine zone of the Alps and accordingly Pinus mugo as the supposedly only larval host plant. The holotype from Switzerland was collected at 1,900 m altitude, and a specimen from the Haller Zunderkopf (Karwendel Mountains, Austria) was swept from P. mugo. Pinus sylvestris , which was additionally taken into consideration (Schedl 1978, Blank 2002), should be excluded, because it is absent in the subalpine zone of the central Alps. : Published as part of Blank, Stephan M., Shinohara, Akihiko & Altenhofer, Ewald, 2013, The Eurasian species of Xyela (Hymenoptera, Xyelidae): taxonomy, host plants and distribution , pp. 1-106 in Zootaxa 3629 (1) on pages 54-55, DOI: 10.11646/zootaxa.3629.1.1, http://zenodo.org/record/5261330 : {"references": ["Benson, R. B. (1961) The sawflies (Hymenoptera Symphyta) of the Swiss National Park and surrounding area. Ergebnisse der wissenschaftlichen Untersuchungen im Schweizerischen Nationalpark, 7, 161 - 195.", "Rasnitsyn, A. P. (1965) Notes on the biology, systematics and phylogeny of Xyelinae (Hymenoptera, Xyelidae). Polske Pismo Entomologiczne, 35 (12), 483 - 519.", "Benson, R. B. (1960) Two new European species of Xyela Dalman (Hymenoptera: Xyelidae). Proceedings of the Entomological Society of London, ser. B (7 - 8), 110 - 112.", "Schedl, W. (1978) Die Xyelidae Europas (Insecta: Hymenoptera, Symphyta, Xyelidae) mit besonderer Berucksichtigung der Fundnachweise aus den Ostalpen. Berichte des Naturwissenschaftlich-Medizinischen Vereins in Innsbruck, 65, 97 - 115.", "Viitasaari, M. (1980) The taxonomy and synonymy of some eastern Fennoscandian sawfly species (Hymenoptera, Symphyta). Notulae Entomologicae, 60 (3), 113 - 116.", "Blank, S. M. (2002) The Western Palaearctic Xyelidae (Hymenoptera). In: Viitasaari, M. (ed.) Sawflies (Hymenoptera, Symphyta) I. A review of the suborder, the Western Palaearctic taxa of Xyeloidea and Pamphilioidea. Tremex Press, Helsinki, pp. 197 - 233."]}